The Impact of Dabigatran and Rivaroxaban on Variation of Platelet Activation Biomarkers and DRT Following Percutaneous Left Atrial Appendage Closure - Xiaoye Li; Xiaochun Zhang; Qinchun Jin; Yanli Li; Daxin Zhou; Qianzhou Lv; Junbo Ge (Frontiers Media S.A., 2021)
Background: The current post-procedure antithrombotic recommendation for left atrial appendage closure (LAAC) remains empiric. This study was designed to compare variations in platelet activation biomarkers and device-related thrombosis (DRT) under different antithrombotic regimens following LAAC.Methods: This study enrolled 105 consecutive patients with atrial fibrillation who underwent LAAC successfully and received post-procedure anticoagulation with either dabigatran (N = 33) or rivaroxaban (N = 72). After 3 months of anticoagulation treatment, thromboelastogram was used to evaluate thrombin receptor-activating peptide (TRAP)-induced platelet aggregation (PA). Measurements of platelet activation biomarkers, including thrombin-antithrombin complex (TAT), P-selectin, von Willebrand disease (vWF), and CD40L, were performed immediately before the LAAC procedure and after 3 months of post-procedure anticoagulation. Repeated transesophageal echocardiography was performed to evaluate DRT during follow-ups.Results: Three (4.2%) patients in the rivaroxaban and 4 (12.1%) patients in the dabigatran group experienced DRT events (odds ratio (OR) = 0.315, 95% confidence interval (95%CI): 0.066-1.489, p = 0.129) during follow-ups. The TRAP-induced PA was statistically significantly higher in the dabigatran group (62.9% vs 59.7%, p = 0.028*). Statistically significant increases in plasma concentration of TAT, P-selectin, and vWF were observed after 3 months of exposure to dabigatran when compared with rivaroxaban. An increased expression of platelet activation biomarkers was observed in DRT subjects compared with non-DRT subjects in terms of P-selectin and vWF (65.28 ± 13.93 ng/L vs 32.14 ± 12.11 ng/L, p = 0.037; 501.92 ± 106.48 U/L vs 280.98 ± 54.10 U/L, p = 0.045; respectively). Multivariate regression analysis indicated that the use of dabigatran might be an independent predictor of DRT (p = 0.022; OR = 4.366, 95%CI: 0.434-10.839). Furthermore, the CHA2DS2-VASc score (OR = 2.076, p = 0.016) and CD40L levels (OR = 1.015, p = 0.021) were independent predictors of increased D-dimer levels.Conclusions: Post-LAAC anticoagulation with dabigatran may increase the risk of DRT by enhancing platelet reactivity. In light of this potential increased risk in DRT, the authors recommend against using dabigatran for post-procedural anticoagulation in patients who have undergone LAAC.